The Management of Post-appendectomy Abscess in Children; A Historical Cohort Study and Update of the Literature - van Amstel, Paul; The, Sarah-May M. L.; M. Mulder, Irene; Bakx, Roel; Derikx, Joep P. M.; van Schuppen, Joost; de Vries, Ralph; van der Kuip, Martijn; Zijp, Gerda W.; Allema, Jan Hein; Bijlsma, Taco S.; van Heurn, L. W. Ernest; et al. (Frontiers in Pediatrics, 2022)
Introduction: Recent studies have shown that specific cases of post appendectomy abscess (PAA) in children could be treated conservatively. However, due to the lack of high-quality evidence, choice of treatment still depends on preferences of the treating surgeon, leading to heterogeneity in clinical practice. Therefore, we aimed to provide an update of recent literature on the management of PAA in children and subsequently evaluate the outcomes of a large multicenter cohort of children treated for PAA. Methods: A literature search was performed in Pubmed and Embase, selecting all randomized controlled trials, prospective and retrospective cohort studies, and case series published from 2014 and onwards and reporting on children (<18 years) treated for a PAA. Subsequently, a historical cohort study was performed, including all children (<18 years) treated for a radiologically confirmed PAA between 2014-2021 in a tertiary referral center and two large peripheral centers. Medical charts were reviewed to compare non-invasive (i.e., antibiotics) and invasive (i.e., drainage procedures) treatment strategies. Primary outcome was the success rate of treatment, defined as no need for further interventions related to PAA or its complications. Results: The search yielded 1991 articles, of which three were included. Treatment success ranged between 69-88% and 56-100% for non-invasive and invasive strategies, respectively. Our multicenter cohort study included 70 children with a PAA, of which 29 (41%) were treated non-invasively and 41 (59%) invasively. In the non-invasive group, treatment was effective in 21 patients (72%) compared to 25 patients (61%) in the invasive group. Non-invasive treatment was effective in 100% of unifocal small (<3 cm) and 80% of unifocal medium size PAA (3-6 cm), but not effective for multiple abscesses. In our tertiary center, 12 of 19 (63%) patients were treated according to a step-up approach. Conclusion: Non-invasive treatment of especially unifocal small and medium size (< 6 cm) PAA in children seems to be safe and effective. Based on these results, a standardized treatment protocol was developed. Prospective validation of this step-up approach-based treatment protocol is recommended.